(untitled) (Transport systems and technologies, 2021)
The study of the energy characteristics of the active traction converter with pulse-width modulation as part of the traction electric drive of an AC electric locomotive was held during the research. Active traction converter provides pulse-width control of the collector DC traction motors voltage and belongs to the basic AC / DC circuit. The transient process when switching transistor switches is accompanied by significant voltage surge, due to the scattering inductance reaction of the traction transformer. Studies have shown that the diode discharge buffer circuits do not provide discharge of the electromagnetic energy accumulated in the winding of the transformer. An active traction converter control algorithm has been developed, which implies the use of pulse-width and phase regulation of rectified voltage. Switching of transistor switches occurs in the presence of a parallel current circuit. This creates the conditions for the discharge of electromagnetic energy accumulated in the secondary winding circuit of the traction transformer. The developed mathematical model allows to investigate the electromagnetic processes that occur during the switching of transistor switches and to evaluate the energy efficiency of the electric locomotive with active traction converter. In the simulation process, the influence of active traction converter parameters and control algorithms on the power rate of the converter, the total THD distortion rate of current and voltage and the relative values of the rectified voltage were investigated. Measures to increase the power rate and to reduce the emission level of higher current harmonics into the traction network were proposed.